2016
DOI: 10.1007/s00167-016-4033-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging classification of haemodialysis-related amyloidosis of the shoulder: risk factors and arthroscopic treatment

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Although the glenohumeral joint capsule may be thickened on MRI in adhesive capsulitis, findings of amyloidosis in the shoulder may be differentiated by thickening of the substance of the rotator cuff, infiltration of fibrous tissue, and eventual rupture of the rotator cuff. Ando et al 29 proposed an MRI-based classification system for hemodialysis-related amyloidosis of the shoulder (Table 1). The diagnosis of amyloidosis is established histologically.…”
Section: Rotator Cuff Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Although the glenohumeral joint capsule may be thickened on MRI in adhesive capsulitis, findings of amyloidosis in the shoulder may be differentiated by thickening of the substance of the rotator cuff, infiltration of fibrous tissue, and eventual rupture of the rotator cuff. Ando et al 29 proposed an MRI-based classification system for hemodialysis-related amyloidosis of the shoulder (Table 1). The diagnosis of amyloidosis is established histologically.…”
Section: Rotator Cuff Diseasementioning
confidence: 99%
“…At a mean of 29.8 months follow-up, satisfactory pain relief was seen in 34 of 36 shoulders, with the mean Japanese Orthopaedic Surgery Association shoulder score improving from 66.4 preoperatively to 86.6 postoperatively. 30 Ando et al 29 suggested that grade 1 and 2 cases may benefit from arthroscopic synovectomy and débridement, whereas complete resections may be technically difficult in grade 3 cases. Outcomes of arthroscopic synovectomy and débridement in Ando et al grade 4 cases have not been reported, and these cases may benefit from open synovectomy and débridement and reverse total shoulder arthroplasty.…”
Section: Rotator Cuff Diseasementioning
confidence: 99%
“…Several measurement methods have been developed to quantify the amount of humeral bone loss [17,18,23,37,39,49]. However, the accuracy and reproducibility of these methods when using diferent imaging modalities have been underinvestigated, and no consensus has been established to date [4,41,46].…”
Section: Introductionmentioning
confidence: 99%
“…Fig 4. The measurement technique according to Flatow et al The diameter of the humeral head is irst measured without the HSL using a line parallel to the articular surface of the glenoid.…”
mentioning
confidence: 99%